Thyrotrophin receptor antibody concentration and activity, several years after treatment for Graves' disease. (17th December 2018) - Nalla, Preethi; Young, Stuart; Sanders, Jane; Carter, Joanne; Adlan, Mohamed A.; Kabelis, Katarzyna; Chen, Shu; Furmaniak, Jadwiga; Rees Smith, Bernard; Premawardhana, Lakdasa D. K. E.
Summary: Objective: TSH receptor antibodies (TRAb) are responsible for autoimmune hyperthyroid disease (Graves' disease; GD) with TRAb levels tending to decrease following treatment. Measurement of TRAb activity during follow‐up could prove valuable to better understand treatment effectiveness. Study design: TRAb concentration and stimulating (TSAb) and blocking (TSBAb) activity of patient serum were assessed following different treatment modalities and follow‐up length. Methods: Sixty‐six subjects were recruited following treatment with carbimazole (n = 26), radioiodine (n = 27) or surgery (n = 13). TRAb, TPOAb, TgAb and GADAb were measured at a follow‐up visit as well as bioassays of TSAb and TSBAb activity. Results: Forty‐five per cent of all patients remained TRAb‐positive for more than one year and 23% for more than 5 years after diagnosis, irrespective of treatment method. Overall, TRAb concentration fell from a median (IQR) of 6.25 (3.9‐12.7) to 0.65 (0.38‐3.2) U/L. Surgery conferred the largest fall in TRAb concentration from 11.4 (6.7‐29) to 0.58 (0.4‐1.4) U/L. Seventy per cent of TRAb‐positive patients were positive for TSAb, and one patient (3%) was positive for TSBAb. TRAb and TSAb correlated well ( r  = 0.83). In addition, 38/66 patients were TgAb‐positive, 47/66 were TPOAb‐positive and 6/66 were GADAb‐positive at follow‐up. Conclusions: TRAb levels generally decreased after treatment but persisted for over 5 years in some patients. TRAb activity was predominantly stimulatory, with only one patient demonstrating TSBAb. A large proportion of patients were TgAb/TPOAb‐positive at follow‐up. All treatment modalities reduced TRAb concentrations; however, surgery was most effective.